The relevance of the cosmological constant for lensing - Ishak, Mustapha; Rindler, Wolfgang (General relativity and gravitation, 2010)
This review surveys some recent developments concerning the effect of the cosmological constant on the bending of light by a spherical mass in Kottler (Schwarzschild–de Sitter) spacetime. Some proposals of how such an effect may be put into a setting of gravitational lensing in cosmology are also discussed. The picture that emerges from this review is that it seems fair to assert that the contribution of Λ to the bending of light has by now been well established, while putting the Λ light-bending terms into a cosmological context is still subject to some interpretation and requires further work and clarification.